Role of Bhrikuti (Bhelsa Tritsun) in Spread of Buddhism (SIRJANĀ – A Journal Of Arts and Art Education, 2017)
The discovery of Mauryan Emperor Ashokan pillar in Lumbini by General Khadaga Shumsher Rana and Dr. Alois Fuhrer in 1896 A.D. opened the door of archaeological study in Nepal. Since then the archaeological excavations have been carried regularly. This article focuses around Lumbini the Birth Place of Buddha and highlights the contributions of Bhrikuti in spreading Buddhism in Tibet.